3(x-4)(x-4)=

Simple and best practice solution for 3(x-4)(x-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)(x-4)= equation:


Simplifying
3(x + -4)(x + -4) = 0

Reorder the terms:
3(-4 + x)(x + -4) = 0

Reorder the terms:
3(-4 + x)(-4 + x) = 0

Multiply (-4 + x) * (-4 + x)
3(-4(-4 + x) + x(-4 + x)) = 0
3((-4 * -4 + x * -4) + x(-4 + x)) = 0
3((16 + -4x) + x(-4 + x)) = 0
3(16 + -4x + (-4 * x + x * x)) = 0
3(16 + -4x + (-4x + x2)) = 0

Combine like terms: -4x + -4x = -8x
3(16 + -8x + x2) = 0
(16 * 3 + -8x * 3 + x2 * 3) = 0
(48 + -24x + 3x2) = 0

Solving
48 + -24x + 3x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3'.
3(16 + -8x + x2) = 0

Factor a trinomial.
3((4 + -1x)(4 + -1x)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {4, 4}

See similar equations:

| 5(2X-8)+6=4x-32 | | 4/3m= | | -16+5(-4)-9=x | | e^3x+2=40 | | -sx=-15 | | 18(5c-1)-2=88c+18 | | 22=A+4B-4C | | (12-3+25)6+20-(10+10)= | | (-7-1x)(5-1x)=0 | | 1-3x=22 | | 8=z/4=23 | | -36=-2A-9B+C | | -11-18-4w/5 | | 7(7+25)+(5+6)10= | | 2x-1+5+x=180 | | 8-1/7u5 | | 20+2y-5=9y-13-3y | | 26=4A+2B | | 3(4+25)-12+-15= | | -6x+20=4x-30 | | 18x+12y=165 | | (2a^-5b^4c^3)^-2/(3a^3b^-7c^3)^2 | | A^2-3a-45=0 | | A^2-3a-34=0 | | 3/8v3 | | x^2+4x-10= | | 10(x+3)=31 | | 111-4u/3 | | 180*(n-2)=1 | | 6sin^2x+9sinx+3=0 | | 5d=3m-14 | | -2v/7-10-15 |

Equations solver categories